(3GdeSJWGHs - (3edG GdOhdI GdSeGf , CMeO Hf eMeO Hf GdHHfGHcj, CHhGdecGQes
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdUfa GdChd aj GdGUWdGMGJ GdJj dGHO ddeSJajO s
(3BNQgG (B:s
(3hbGd GHf YWGA efge ef GJHY GdJj Udj Gddg Ydjg hSde aj GdXGgQ hefge ef GJHYg Ydi GdMbjbI hGdJMbjb s
(3HgG fXGe GdJYbjHIs
(3hChd UaMGJgG HgG GgJRGR TOjO ef Ndd MOK aj GdJUhjQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs